On scandal and scandals: the psychology of clerical paedophilia. - Callaghan, Brendan (Studies: An Irish Quarterly)
The article offers information on the social implication caused by clerical sexual abuse in the Catholic Church. It focuses on the massive emotional damage to the abused and the social reaction that creates intelligent reflection and anger. It presents the vital facts on the role and impact of the Roman Catholic Church's governances including mandatory celibacy and conspiracy of silence, and the government's social responsibility and actions.